Insights into the epidemiology, risk factors, and clinical outcomes of carbapenem-resistant Acinetobacter baumannii infections in critically ill children - Yufei Zhang; Guifeng Xu; Fei Miao; Weichun Huang; Haiying Wang; Xing Wang (Frontiers Media S.A., 2023)
Background and aimsCarbapenem-resistant Acinetobacter baumannii (CRAB) has become a leading cause of nosocomial infections with an increasing impact on critically ill patients, yet there is limited data on contributing factors. This study was aim to evaluate the prevalence and risk factors, and clinical outcomes of CRAB infections among critically ill children in a tertiary university teaching hospital in China.MethodsFrom January 2016 to December 2021, all children diagnosed with nosocomial Acinetobacter baumannii (A. baumannii) infections in the pediatric intensive care unit (PICU) were identified through the computerized microbiology laboratory databases. Among them, children suffering from CRAB infection were designated as a case group, while children with carbapenem susceptible A. baumannii (CSAB) infection were assigned to a control group. This retrospective case-control study was based on two groups of patients to determine potential clinical factors contributing to CRAB infection and death among critically ill children via univariate and multivariate analyses.ResultsDuring the 6-year study period, a total of 372 episodes of nosocomial A. baumannii infection in the PICU were eligible and included in the study. These isolates displayed moderate or high rates of resistance to all tested antimicrobials except colistin. The overall prevalence of CRAB and MDRAB (multidrug-resistant A. baumannii) was 78.0% and 80.9%, respectively. Several risk factors found to significantly increase CRAB infection included receiving invasive operation (OR = 9.412, p = 0.001), gastric intubation (OR = 2.478, p = 0.026), prior carbapenems exposure (OR = 2.543, p = 0.003), severe pneumonia (OR = 3.235, p = 0.001), and hemoglobin <110g/L (OR = 3.049, p = 0.005). Of 372 patients with CRAB infection, the mortality rate was 30.9% (115/372) and mortality did not differ between children with CRAB and CSAB infections. Septic shock (OR = 2.992, p = 0.001), AST > 46U/L (OR = 2.015, p = 0.005), bone marrow aspiration (OR = 2.704, p = 0.008), lymphocyte <20 % (OR = 1.992, p = 0.006) and age (OR = 1.094, p = 0.002) were independent risk factors for the death of A. baumanni infection.ConclusionsThis study highlights considerable incidence rate and remarkable mortality of children with A. baumanni (especially CRAB) infections, and identifies age-specific risk factors for CRAB infection and mortality in critically ill children. These risk factors should be taken into account in pediatric hospitals in order to establish early intervention and rational treatment to improve clinical outcomes.